Lyapunov Functional for Lateral Buckling of I Beams Subjected to Pure Bending - Akeju, T.A. (Engineering Transactions, 1982)
Lateral buckling of I beams subjected to pure bending is investigated by the direct method of Laypunov. A metric space and an energy type Lyapunov functional are proposed for the solution of the problem. These readily yield familiar expressions for the buckling loads of simply supported and fixed ended beams.